A survey on general and temperature management of post cardiac arrest patients in large teaching and university hospitals in 14 European countries—The SPAME trial results. (July 2017) - Storm, Christian; Nee, J.; Sunde, Kjetil; Holzer, Michael; Hubner, Pia; Taccone, Fabio Silvio; Friberg, Hans; Lopez-de-Sa, Esteban; Cariou, Alain; Schefold, Joerg C.; Ristagno, Giuseppe; Noc, Marko; et al.
Abstract: Introduction: International guidelines recommend a bundle of care, including targeted temperature management (TTM), in post cardiac arrest survivors. Aside from a few small surveys in different European countries, adherence to the European Resuscitation Council (ERC) and European Society of Intensive Care Medicine (ESICM) recommendations are unknown. Methods: This international European telephone survey was conducted to provide an overview of current clinical practice of post cardiac arrest management with a main focus on TTM. We targeted large teaching and university hospitals within Europe as leading facilities and key opinion leaders in the field of post cardiac arrest care. Selected national principal investigators conducted the survey, which was based on a predefined questionnaire, between December 2014 and March 2015, before the publication of the ERC Guidelines 2015. Results: The return rate was 94% from 268 participating intensive care units (ICU). The majority had a predefined standard operating procedure (SOP) protocol for post cardiac arrest patients. Altogether, 68% of the ICUs provided TTM at a target temperature of 32–34 °C for 24 h, and 33% had changed the target temperature to 36 °C. The minority provided a written SOP for neurological prognostication, which was generally initiated 72 h after return of spontaneous circulation (ROSC). Electroencephalography and somatosensory evoked potentials were used by most ICUs for early prognostication. Treating more than fifty patients a year was significantly associated with providing written SOPs for TTM and prognostication (p < 0.01), as well as the use of a computer feedback device (p = 0.03) for TTM. Conclusion: This international European telephone survey revealed a high rate of implementation of TTM in post cardiac arrest patients in university and teaching hospitals. Most participants also provided a SOP, but only a minority had a SOP for neurological prognostication.